Immunophenotype of a Rat Model of Duchenne's Disease and Demonstration of Improved Muscle Strength After Anti-CD45RC Antibody Treatment - Ouisse, Laure-Hélène; Remy, Séverine; Lafoux, Aude; Larcher, Thibaut; Tesson, Laurent; Chenouard, Vanessa; Guillonneau, Carole; Brusselle, Lucas; Vimond, Nadège; Rouger, Karl; Péréon, Yann; Chenouard, Alexis; et al. (Frontiers in Immunology, 2019)
Corticosteroids (CS) are standard therapy for the treatment of Duchenne’s muscular dystrophy (DMD). Even though they decrease inflammation, they have limited efficacy and are associated with significant side effects. There is therefore the need for new protolerogenic treatments to replace CS. Dystrophin-deficient rats (Dmdmdx) closely resemble the pathological phenotype of DMD patients. We performed the first Immunophenotyping of Dmdmdx rats and showed leukocyte infiltration in skeletal and cardiac muscles, which consisted mostly of macrophages and T cells including CD45RChigh T cells. Muscles of DMD patients also contain elevated CD45RChigh T cells. We treated Dmdmdx rats with an anti-CD45RC Mab used in previous studies to deplete CD45RChigh T cells and induce immune tolerance in models of organ transplantation. Treatment of young Dmdmdx rats with anti-CD45RC MAb corrected skeletal muscle strength and was associated with depletion of CD45RChigh T cells with no side effects. Treatment of young Dmdmdx rats with prednisolone resulted in increase in skeletal muscle strength but also severe growth retardation. In conclusion, anti-CD45RC MAb treatment has potential in the treatment of DMD and might eventually result in reduction or elimination of CS use.